IoT-BASED SMART GARDEN USING MQTT PROTOCOL WITH ADAFRUIT IO APP - Syafaat, Muhammad; Ramadhan, Armansyah Nur; Syafiun, Ruhman Bani; Haerunnisa, Dian Aprilia (Informatika, Universitas Jenderal Soedirman, 2023)
During the COVID-19 pandemic, more community activities were at home with government policies to limit people's movements, especially in urban areas. During the period of restrictions on people's movements due to COVID-19, it was also followed by new habits, namely activities around the house, one of which was the increasing trend of Urban Farming to fill time. However, after the pandemic began to experience a downward trend, people no longer cared for their plants due to activities that had returned to normal. In this research, the design of Internet of Things technology was carried out to help urban communities to monitor and control plants so that people continue to carry out their daily activities without worrying about their plants running out of water. This study uses the NodeMCu V3 microcontroller as the data receiving center at the hardware layer and then a DHT 11 sensor is needed for temperature monitoring, a Soil Moisture sensor for monitoring soil moisture, a raindrop sensor for monitoring rain conditions as well as relays and a mini pump to control the water needs of plants. The results of this study are that the IoT device successfully displays temperature data, soil moisture data, rain status and automatic plant watering controls function properly if the value on the soil moisture sensor is below 25. The data communication path in this study uses the MQTT protocol using a webserver from Adafruit IO with an average packet loss of 0.20%. With the functioning of all the components on the created IoT device, the community can apply an IoT-based Smart Garden in urban farming so that plant maintenance can still be carried out.